Pharmacokinetics and tolerability of MB12066, a beta-lapachone derivative targeting NAD(P)H:quinone oxidoreductase 1: two independent, double-blind, placebo-controlled, combined single and multiple ascending dose first-in-human clinical trials - Kim S; Lee S; Cho JY; Yoon SH; Jang IJ; Yu KS (Dove Medical Press, 2017)
Seokuee Kim,1,2 SeungHwan Lee,1,3 Joo-Youn Cho,1,3 Seo Hyun Yoon,1,3 In-Jin Jang,1,3 Kyung-Sang Yu1,31Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine, 2Department of Clinical Pharmacology and Therapeutics, Samsung Medical Center, 3Department of Clinical Pharmacology and Therapeutics, Seoul National University Hospital, Seoul, KoreaAbstract: MB12066 is a molecule derived from β-lapachone that shown effects on obesity in previous studies. The present studies were conducted to evaluate the tolerability and pharmacokinetics (PK) of MB12066 after the oral administration of single and multiple doses to healthy volunteers. The study comprised 2 independent, randomized, double-blind, placebo-controlled, combined single and multiple ascending dose first-in-human clinical trials to evaluate the safety, tolerability and PK of MB12066 in healthy Korean volunteers. Subjects were randomly assigned to receive a single 10, 30, 100, 150, 200, 300 or 400 mg of MB12066 and multiple 100 or 200 mg of MB12066. The subjects’ vital signs, 12-lead electrocardiograms, clinical laboratory tests, adverse event statuses, and physical examinations were assessed during the study. Blood and urine samples were collected to determine the concentration of MB12066 from predose to 72 hours after the single administration and from predose to 96 hours postdose of day 7 after the multiple administration. NADH:quinone oxidoreductase 1 genotyping was performed to analyze the association between genetic polymorphisms and PK. MB12066 was well tolerated after oral administration of single and multiple doses. The systemic exposure to MB12066 after a single administration tended to increase in a dose-dependent manner in the dose range of 30–200 mg. The overall fraction of MB12066 excreted unchanged in urine was <1% of the administered dose. A significant relationship was observed between NADH:quinone oxidoreductase 1 polymorphisms and exposure to MB12066 after multiple administrations, but the result was not conclusive because of the small number of subjects. A single dose of MB12066 within the dose range of 10–400 mg and multiple doses of 100 and 200 mg of MB12066 were safe and tolerated in healthy subjects. Additionally, MB12066 was mainly eliminated through metabolism in humans.Keywords: pharmacokinetics, Phase I, first-in-human, NQO1, pharmacogenomics